Degradable antibacterial intelligent color-changing printing packaging material and preparation method thereof

By regulating the stereoregulation and D-isomer content of PLLA and PDLA, pH-sensitive copolymers and surface-modified nanosilver are developed, and the precise temperature-shear coupling control system is adopted to solve the brittleness of intelligent packaging materials. The problems of high thermal instability and difficult to coordinate degradation and mechanical properties have achieved efficient antibacterial performance and rapid color discoloration response.

CN119391155AActive Publication Date: 2025-02-07JINGCHU UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411685690.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-02-07
Estimated Expiration
2044-11-23

AI Technical Summary

Technical Problem

Existing smart packaging materials have problems such as high brittleness, poor thermal stability, difficult to coordinate degradation and mechanical properties, slow response of pH-sensitive infection materials, poor dispersion of nanosilver and lack of synergistic effects between functional components.

Method used

By regulating the stereoregulation and D-isomer content of PLLA and PDLA, pH-sensitive copolymers and surface-modified nanosilver are developed, and precise temperature-shear coupling control system is adopted to realize the orientation arrangement of the multi-component system and Selective crystallization.

Benefits of technology

It improves the crystallinity, thermal stability and antibacterial properties of the material, achieves rapid and reversible color discoloration response, and significantly improves the degradation and comprehensive performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005149399050000181
    Figure BDA0005149399050000181
  • Figure BDA0005149399050000191
    Figure BDA0005149399050000191
  • Figure BDA0005149399050000192
    Figure BDA0005149399050000192
Patent Text Reader

Abstract

The invention relates to the technical field of color-changing printing packaging materials, in particular to a degradable antibacterial intelligent color-changing printing packaging material and a preparation method thereof.The degradable antibacterial intelligent color-changing printing packaging material is prepared from, by weight, 63-67 parts of a blend of PLLA and PDLA, the mass ratio of the PLLA to the PDLA is 70: 30-90: 10; 19-21 parts of a P (3HB-co-4HB) copolymer, wherein the molar ratio of 3HB to 4HB is 85: 15 to 95: 5; 17 to 18 parts of modified starch; 3.4 to 3.8 parts of surface modified nano silver; 7.7 to 8.3 parts of a pH sensitive dye system; 8.0 to 8.6 parts of a silane coupling agent KH550; the crystallinity and the thermal stability of the material are improved by regulating and controlling the stereoregularity and the D-isomer content of the PLLA and the PDLA and utilizing a stereocomplex effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of color-changing printing and packaging materials, and in particular to a degradable, antibacterial, intelligent color-changing printing and packaging material and a preparation method thereof. Background Art

[0002] With the increasing awareness of environmental protection and the improvement of food safety requirements, the development of bio-based smart packaging materials has become a current research hotspot. In the existing technology, polylactic acid (PLA) has been widely studied due to its good biocompatibility and processability. However, PLA has inherent defects such as high brittleness and poor thermal stability. Although the performance of PLA can be improved to a certain extent by blending modification, the current modification methods often lose one thing while gaining the other: toughening modification will reduce the degradation performance of the material, while improving the degradability will often sacrifice the mechanical properties.

[0003] In addition, most of the smart packaging materials on the market currently use the method of direct blending or loading of pH-sensitive dyes, which has serious problems of dye migration and shedding. Although some researchers have tried to introduce pH-sensitive groups into polymer chains by chemical grafting, it is difficult to achieve large-scale production due to harsh reaction conditions and complex processes. At the same time, the pH response of such materials is often slow and the sensitivity is insufficient, which cannot meet the needs of practical applications.

[0004] In terms of antibacterial properties, existing technologies mostly use the method of simply adding nanosilver. However, since nanosilver is easy to agglomerate, its dispersibility and stability are poor, which not only affects the antibacterial effect, but also leads to uneven material properties. Although there are studies on improving the dispersibility of nanosilver by using surfactants, this method will introduce new compatibility issues, and the presence of surfactants may affect the food contact safety of the material.

[0005] There is also a common problem in the existing technology, that is, the lack of synergy between functional components. For example, the addition of antimicrobial agents may affect the response performance of pH-sensitive dyes, while the introduction of toughening agents may reduce the gas barrier properties of the material. This phenomenon of "taking care of one thing and losing the other" seriously restricts the practical application of smart packaging materials. Summary of the invention

[0006] In view of the above problems, the present invention provides a degradable antibacterial intelligent color-changing printing packaging material and a preparation method thereof.

[0007] The object of the present invention is to provide a degradable antibacterial intelligent color-changing printing packaging material, which comprises the following components in parts by weight:

[0008] 63-67 parts of a blend of PLLA and PDLA, wherein the mass ratio of PLLA to PDLA is 70:30 to 90:10;

[0009] 19-21 parts of a P(3HB-co-4HB) copolymer, wherein the molar ratio of 3HB to 4HB is 85:15 to 95:5;

[0010] 17-18 parts of modified starch;

[0011] 3.4-3.8 parts of surface modified nanosilver;

[0012] 7.7-8.3 parts pH sensitive dye system;

[0013] 8.0-8.6 parts of silane coupling agent KH550;

[0014] 6.9-7.5 parts of kaolin.

[0015] Preferably, the blend of PLLA and PDLA has a D-isomer content of 0.5-2%, a stereoregularity of 98-99.5%, and a weight average molecular weight of 100,000-150,000.

[0016] Preferably, the molecular weight distribution of the P(3HB-co-4HB) copolymer is 1.8-2.2, and the crystallinity is 55-65%.

[0017] Preferably, the modified starch comprises the following components by weight:

[0018] 21-23 parts of corn starch, wherein the amylose content is 23-27%;

[0019] 6.5-7.5 parts of surface-modified nano-CaCO3 with a particle size of 40-60 nm;

[0020] 1.8-2.2 parts of hydroxymethyl cellulose, with a degree of substitution of 1.6-2.0;

[0021] 7.5-8.5 parts deionized water.

[0022] Preferably, the pH sensitive dye system is compounded by a copolymer obtained by free radical polymerization of the following monomers in parts by weight and acid violet 49 in a mass ratio of 3.5:1 to 4.5:1:

[0023] 43-47 parts of styrene;

[0024] 33-37 parts of acrylic acid;

[0025] 19-21 parts of 2-aminoethyl 2-methacrylate;

[0026] 0.45-0.55 parts AIBN.

[0027] The method for preparing the degradable antibacterial intelligent color-changing printing packaging material comprises the following steps:

[0028] (1) Preparation of modified starch:

[0029] a) mixing corn starch with deionized water at 115-120° C. and 0.18-0.22 MPa, and stirring at a rate of 210-230 rpm for 33-37 min;

[0030] b) adding surface-modified nano-CaCO3 and hydroxymethyl cellulose, heating to 135-145°C, stirring at 230-250 rpm for 38-42 min at 0.28-0.32 MPa;

[0031] (2) Preparation of surface modified nanosilver:

[0032] a) using 0.01-0.02 mol / L silver nitrate as raw material, using 0.5-1.0 wt% PVP as protective agent, reacting at 78-82° C. for 28-32 min;

[0033] b) adding 2-3 wt% of mercaptosilane coupling agent KH590 and modifying at 58-62° C. for 3.5-4.5 h;

[0034] (3) Preparation of pH sensitive dye system:

[0035] Free radical polymerization was carried out at 73-77°C under nitrogen protection at a stirring rate of 170-190 rpm for 5.5-6.5 h, followed by compounding with Acid Violet No. 49 at 48-52°C for 1.8-2.2 h;

[0036] (4) Matrix material blending:

[0037] The modified PLA and the modified PHA were stirred at a rate of 220-240 rpm for 38-42 min at 175-185° C. and a vacuum degree of -0.05 to -0.07 MPa;

[0038] (5) Functional component combination:

[0039] Modified nanosilver, pH-sensitive dye system, coupling agent KH550 and kaolin were added in sequence, and a stepwise heating program was adopted:

[0040] a) 180℃ to 200℃, heating rate 1.8-2.2℃ / min;

[0041] b) 200°C to 250°C, heating rate 0.8-1.2°C / min;

[0042] c) Keep at 240-260°C for 28-32 minutes.

[0043] Preferably, the dispersion process in step (5) adopts a shear control procedure:

[0044] The initial shear rate is 45-55s-1,

[0045] The termination shear rate is 190-210s-1,

[0046] The linear increase time is 14-16min.

[0047] Preferably, the vacuum control procedure in step (5) is:

[0048] The initial vacuum degree is -0.018 to -0.022MPa,

[0049] The final vacuum degree is -0.058 to -0.062MPa.

[0050] The vacuuming time is 18-22 minutes.

[0051] Preferably, the cooling procedure after step (5) is:

[0052] 250℃ to 180℃, cooling rate 2.8-3.2℃ / min;

[0053] 180℃ to 100℃, cooling rate 4.8-5.2℃ / min;

[0054] Natural cooling is adopted below 100℃.

[0055] Preferably, the preparation method of the surface-modified nano-CaCO3 is:

[0056] Nano-CaCO3 with a particle size of 40-60 nm and stearic acid with a mass fraction of 1.5-2.0% are stirred at 75-85° C. at a speed of 180-220 rpm for 1.8-2.2 hours.

[0057] The present invention has the following beneficial effects:

[0058] Through molecular design and process innovation, the above technical difficulties were cleverly solved. First, by regulating the stereoregularity and D-isomer content of PLLA and PDLA, the crystallinity and thermal stability of the material were improved by using the stereocomplex effect. At the molecular level, the two configurations of PLA molecular chains formed stable stereocomplex crystals through stereoselective crystallization, which not only improved the strength of the material, but also significantly improved the heat resistance.

[0059] Secondly, the pH-sensitive copolymer developed by the present invention has a unique molecular structure: the hydrophobic styrene unit provides good matrix compatibility, and the acrylic acid and 2-aminoethyl 2-methacrylate units form a dynamic response network through hydrogen bonding. When the environmental pH changes, the protonation / deprotonation process causes a synergistic change in the copolymer chain conformation, thereby achieving a rapid and reversible color change response.

[0060] It is particularly worth mentioning that the present invention has made a breakthrough in the surface modification of nanosilver. Through chemical modification of mercaptosilane coupling agent, an interface layer with a gradient transition structure is constructed on the surface of nanosilver. This interface design not only provides a steric hindrance effect to prevent agglomeration, but also achieves a strong interaction with the matrix through chemical bonding. What is even more surprising is that this surface-modified nanosilver can also form a synergistic effect with pH-sensitive dyes, and enhance the intensity of the color change signal through local plasma resonance.

[0061] At the process level, the present invention has established a precise temperature-shear coupling control system. Through programmed segmented heating and shear regulation, the directional arrangement and selective crystallization of the multi-component system are achieved. This process innovation not only optimizes the microstructure of the material, but also significantly improves the processing stability and reproducibility.

[0062] In summary, the present invention has achieved a synergistic improvement in various material properties through multi-level molecular design and process innovation, successfully breaking through the bottleneck of the existing technology. In particular, the breakthroughs achieved in degradation performance, antibacterial effect, intelligent response, etc. have opened up new avenues for the development of bio-based intelligent packaging materials. These innovations not only solve long-standing technical problems in the industry, but also bring about a number of unexpected synergistic effects, reflecting the important theoretical value and practical application prospects of the present invention. DETAILED DESCRIPTION

[0063] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0064] Example 1

[0065] This embodiment provides a degradable antibacterial intelligent color-changing printing packaging material and a preparation method thereof. In this embodiment, by optimizing the ratio of each component and the preparation process, the material achieves excellent degradability, antibacterial properties and intelligent color-changing function.

[0066] The packaging material comprises the following components by weight: 63 parts of a blend of PLLA and PDLA (mass ratio is 70:30), 19 parts of a P(3HB-co-4HB) copolymer (molar ratio of 3HB to 4HB is 85:15), 17 parts of modified starch, 3.4 parts of surface-modified nanosilver, 7.7 parts of a pH-sensitive dye system, 8.0 parts of a silane coupling agent KH550, and 6.9 parts of kaolin. The D-isomer content of the blend of PLLA and PDLA is 0.5%, the stereoregularity is 98%, and the weight average molecular weight is 100,000. The molecular weight distribution of the P(3HB-co-4HB) copolymer is 1.8, and the crystallinity is 55%.

[0067] The preparation method of the present embodiment comprises the following steps:

[0068] (1) Preparation of modified starch

[0069] First, 21 parts of corn starch (23% amylose content), 6.5 parts of surface-modified nano-CaCO3 (particle size 40nm), 1.8 parts of hydroxymethyl cellulose (degree of substitution 1.6) and 7.5 parts of deionized water were measured by weight. Corn starch and deionized water were mixed at 115°C and 0.18MPa, and stirred at a rate of 210rpm for 33min. Then, surface-modified nano-CaCO3 and hydroxymethyl cellulose were added, the temperature was raised to 135°C, and stirred at a rate of 230rpm for 38min at a pressure of 0.28MPa.

[0070] Preferably, in the preparation process of the modified starch, the surface modification of nano-CaCO3 is carried out by the following method: 40 nm nano-CaCO3 and 1.5% stearic acid are stirred at 75° C. at a rate of 180 rpm for 1.8 h. This modification process significantly improves the compatibility of nano-CaCO3 with the matrix.

[0071] (2) Preparation of surface-modified silver nanoparticles

[0072] A silver nitrate solution with a concentration of 0.01 mol / L was used as a raw material, and 0.5 wt% PVP was added as a protective agent, and the reaction was carried out at 78°C for 28 minutes. Preferably, the nanosilver particle size obtained under this reaction condition is uniformly distributed, which is conducive to improving the antibacterial properties of the material. Subsequently, 2 wt% of mercaptosilane coupling agent KH590 was added and modified at 58°C for 3.5 hours. It is worth noting that the surface modification of the silane coupling agent significantly improved the dispersion stability of nanosilver in the polymer matrix, thereby enhancing the long-term antibacterial properties of the material.

[0073] (3) Preparation of pH-sensitive dye system

[0074] Under nitrogen protection, 43 parts of styrene, 33 parts of acrylic acid, 19 parts of 2-aminoethyl methacrylate and 0.45 parts of AIBN were free radical polymerized for 5.5 hours at 73°C and a stirring rate of 170 rpm. In particular, the selection of this copolymer composition gives the pH-sensitive dye an ideal response sensitivity. Subsequently, the resulting copolymer was compounded with acid violet 49 at a mass ratio of 3.5:1 at 48°C for 1.8 hours to obtain a functional component with excellent pH response performance.

[0075] (4) Matrix material blending

[0076] At 175℃ and vacuum degree -0.05MPa, the modified PLA and modified PHA were stirred at 220rpm for 38min. It is worth noting that under this process condition, PLA and PHA formed an interpenetrating network structure, and this special microstructure significantly improved the toughness of the material.

[0077] (5) Functional component combination

[0078] Using a step-by-step heating program, modified nanosilver, pH-sensitive dye system, coupling agent KH550 and kaolin are added to the matrix material in sequence. Specifically:

[0079] a) First, the temperature was increased from 180°C to 200°C at a rate of 1.8°C / min;

[0080] b) Continue to heat up to 250°C, and adjust the heating rate to 0.8°C / min;

[0081] c) Keep at 240°C for 28 min.

[0082] During the dispersion process, programmed shear control was used: the initial shear rate was 45s-1, the final shear rate was 190s-1, and the linear increase time was 14min. At the same time, the vacuum control program was: initial vacuum degree -0.018MPa, final vacuum degree -0.058MPa, and vacuum time was 18min.

[0083] Finally, a segmented cooling program was adopted: the temperature from 250°C to 180°C was cooled at a rate of 2.8°C / min, the temperature from 180°C to 100°C was cooled at a rate of 4.8°C / min, and natural cooling was used below 100°C. It should be pointed out that this precisely controlled cooling program has an important influence on the final crystallinity and mechanical properties of the material.

[0084] Preferably, the synergistic combination of the polymer matrix, functional filler and preparation process in this embodiment enables the material to have the following characteristics:

[0085] 1) Through the PLA / PHA blending modification and the introduction of modified starch, the biodegradability is significantly improved while ensuring the mechanical properties of the material;

[0086] 2) The combined use of nanosilver and pH-sensitive dyes not only gives the material antibacterial function, but also realizes intelligent monitoring of food freshness;

[0087] 3) The synergistic modification of interfaces in multi-component systems effectively solves the compatibility problems that are common in composite materials.

[0088] Through the above-mentioned optimized component ratio and preparation process, the packaging material prepared in this embodiment has excellent comprehensive performance. In particular, the material's degradability rate reaches 99.8%, the antibacterial rate reaches 90.0%, and the color difference △E*ab of the intelligent color change performance at 5°C reaches 0.1, which fully meets the relevant standard requirements.

[0089] Example 2

[0090] This embodiment also provides a biodegradable antibacterial intelligent color-changing printing packaging material and a preparation method thereof. Compared with Example 1, this embodiment optimizes and adjusts the ratio of each component and the preparation process parameters, further improving the material performance.

[0091] The packaging material comprises the following components by weight: 65 parts of a blend of PLLA and PDLA (mass ratio is 80:20), 20 parts of a P(3HB-co-4HB) copolymer (molar ratio of 3HB to 4HB is 90:10), 17.5 parts of modified starch, 3.6 parts of surface-modified nanosilver, 8.0 parts of a pH-sensitive dye system, 8.3 parts of a silane coupling agent KH550, and 7.2 parts of kaolin. The D-isomer content of the blend of PLLA and PDLA is 1.25%, the stereoregularity is 98.8%, and the weight-average molecular weight is 125,000. Preferably, the molecular weight distribution of the P(3HB-co-4HB) copolymer is 2.0, and the crystallinity is 60%.

[0092] The preparation method of the present embodiment comprises the following steps:

[0093] (1) Preparation of modified starch

[0094] First, 22 parts of corn starch (25% amylose content), 7.0 parts of surface-modified nano-CaCO3 (particle size 50nm), 2.0 parts of hydroxymethyl cellulose (degree of substitution 1.8) and 8.0 parts of deionized water were measured by weight. Corn starch and deionized water were mixed at 117.5℃ and 0.20MPa, and stirred at a rate of 220rpm for 35min. Further, surface-modified nano-CaCO3 and hydroxymethyl cellulose were added, the temperature was raised to 140℃, and stirred at a rate of 240rpm for 40min under a pressure of 0.30MPa. It is worth noting that this modification process significantly improves the compatibility of starch with the polyester matrix.

[0095] In particular, during the preparation of the modified starch, the surface modification of nano-CaCO3 is carried out by the following method: 50 nm nano-CaCO3 and 1.75% stearic acid are stirred at 80° C. at a rate of 200 rpm for 2.0 h.

[0096] (2) Preparation of surface-modified silver nanoparticles

[0097] A 0.015 mol / L silver nitrate solution was selected as the raw material, 0.75 wt% PVP was added as a protective agent, and the reaction was carried out at 80°C for 30 minutes. Subsequently, 2.5 wt% mercaptosilane coupling agent KH590 was added, and the reaction was carried out at 60°C for 4.0 hours. Preferably, by adjusting the reaction conditions, nanosilver particles with uniform particle size and good dispersibility were obtained.

[0098] (3) Preparation of pH-sensitive dye system

[0099] Under nitrogen protection, 45 parts of styrene, 35 parts of acrylic acid, 20 parts of 2-aminoethyl methacrylate and 0.50 parts of AIBN were free radical polymerized at 75°C and 180 rpm for 6.0 h. Further, the obtained copolymer was compounded with acid violet 49 at a mass ratio of 4:1 at 50°C for 2.0 h. This ratio optimization improves the color change sensitivity of the material.

[0100] (4) Matrix material blending

[0101] The modified PLA and modified PHA were stirred at 180℃, vacuum degree -0.06MPa, and speed of 230rpm for 40min. In particular, the selection of such process parameters is conducive to the formation of a stable blending system.

[0102] (5) Functional component combination

[0103] Using the optimized staged heating program, add each functional component in turn:

[0104] a) From 180℃ to 200℃, the heating rate is 2.0℃ / min;

[0105] b) Continue to heat up to 250°C at a heating rate of 1.0°C / min;

[0106] c) Keep at 250°C for 30 min.

[0107] During the dispersion process, an improved shear control program was used: the initial shear rate was 50s-1, the final shear rate was 200s-1, and the linear increase time was 15min. At the same time, the vacuum control program was: initial vacuum degree -0.020MPa, final vacuum degree -0.060MPa, and vacuum time was 20min.

[0108] Finally, an optimized cooling program was adopted: cooling from 250℃ to 180℃ at a rate of 3.0℃ / min, cooling from 180℃ to 100℃ at a rate of 5.0℃ / min, and natural cooling below 100℃.

[0109] Example 3

[0110] This embodiment provides a degradable antibacterial intelligent color-changing printing packaging material with further optimized component ratio and process parameters and a preparation method thereof. Compared with the previous two embodiments, this embodiment focuses on strengthening the antibacterial performance and pH response characteristics of the material.

[0111] The packaging material includes the following components by weight: 66 parts of a blend of PLLA and PDLA (mass ratio is 85:15), 20.5 parts of P (3HB-co-4HB) copolymer (molar ratio of 3HB to 4HB is 92:8), 18 parts of modified starch, 3.7 parts of surface modified nanosilver, 8.2 parts of pH sensitive dye system, 8.5 parts of silane coupling agent KH550 and 7.4 parts of kaolin. Among them, the D-isomer content of the PLLA and PDLA blend is 1.5%, the stereoregularity is 99%, and the weight average molecular weight is 135,000. It is worth noting that the molecular weight distribution of the P (3HB-co-4HB) copolymer is 2.1 and the crystallinity is 62%.

[0112] The preparation method of the present embodiment comprises the following steps:

[0113] (1) Preparation of modified starch

[0114] First, 22.5 parts of corn starch (26% amylose content), 7.2 parts of surface-modified nano-CaCO3 (particle size 55nm), 2.1 parts of hydroxymethyl cellulose (degree of substitution 1.9) and 8.2 parts of deionized water were measured by weight. Corn starch and deionized water were mixed at 118°C and 0.21MPa, and stirred at a rate of 225rpm for 36min. Further, surface-modified nano-CaCO3 and hydroxymethyl cellulose were added, the temperature was raised to 142°C, and stirred at a rate of 245rpm for 41min at a pressure of 0.31MPa.

[0115] Preferably, the surface modification of nano-CaCO3 is carried out by the following method: 55 nm nano-CaCO3 and 1.85% stearic acid are stirred at 82° C. at a rate of 210 rpm for 2.1 h.

[0116] (2) Preparation of surface-modified silver nanoparticles

[0117] Using 0.018 mol / L silver nitrate solution as raw material, adding 0.85 wt% PVP as protective agent, reacting at 81°C for 31 min. Then, adding 2.7 wt% mercaptosilane coupling agent KH590, modifying at 61°C for 4.2 h. Through this optimized process parameters, the dispersion stability of nanosilver is significantly improved.

[0118] (3) Preparation of pH-sensitive dye system

[0119] Under strict nitrogen protection, 46 parts of styrene, 36 parts of acrylic acid, 20.5 parts of 2-aminoethyl methacrylate and 0.52 parts of AIBN were free radical polymerized at 76°C and 185 rpm for 6.2 hours. In particular, the obtained copolymer was compounded with acid violet 49 at a mass ratio of 4.2:1 at 51°C for 2.1 hours.

[0120] (4) Matrix material blending

[0121] Under the conditions of 182°C and vacuum degree of -0.065MPa, the modified PLA and modified PHA were stirred at a rate of 235rpm for 41min.

[0122] (5) Functional component combination

[0123] Using an optimized step-by-step heating program, add each functional component in turn:

[0124] a) From 180℃ to 200℃, the heating rate is 2.1℃ / min;

[0125] b) Continue heating to 250°C at a heating rate of 1.1°C / min;

[0126] c) Keep at 255°C for 31 min.

[0127] During the dispersion process, a refined shear control program was used: the initial shear rate was 52s-1, the final shear rate was 205s-1, and the linear increase time was 15.5min. At the same time, the vacuum control program was: initial vacuum degree -0.021MPa, final vacuum degree -0.061MPa, and vacuum time 21min.

[0128] Finally, a three-stage cooling program was adopted: cooling from 250°C to 180°C at a rate of 3.1°C / min, cooling from 180°C to 100°C at a rate of 5.1°C / min, and natural cooling below 100°C.

[0129] Example 4

[0130] This embodiment demonstrates a biodegradable antibacterial intelligent color-changing printing packaging material with optimized parameter ratio and its preparation method. This embodiment pays special attention to the balance and coordination of various properties of the material.

[0131] The packaging material comprises the following components by weight: 67 parts of a blend of PLLA and PDLA (mass ratio is 90:10), 21 parts of a P(3HB-co-4HB) copolymer (molar ratio of 3HB to 4HB is 95:5), 18 parts of modified starch, 3.8 parts of surface-modified nanosilver, 8.3 parts of a pH-sensitive dye system, 8.6 parts of a silane coupling agent KH550, and 7.5 parts of kaolin. In particular, the D-isomer content of the PLLA and PDLA blend is 2%, the stereoregularity is 99.5%, and the weight-average molecular weight is 150,000. The molecular weight distribution of the P(3HB-co-4HB) copolymer is 2.2, and the crystallinity is 65%.

[0132] The preparation method of the present embodiment comprises the following steps:

[0133] (1) Preparation of modified starch

[0134] First, 23 parts of corn starch (27% amylose content), 7.5 parts of surface-modified nano-CaCO3 (60 nm in particle size), 2.2 parts of hydroxymethyl cellulose (2.0 degree of substitution) and 8.5 parts of deionized water were measured by weight. Corn starch and deionized water were mixed at 120°C and 0.22 MPa and stirred at 230 rpm for 37 min. Further, surface-modified nano-CaCO3 and hydroxymethyl cellulose were added, the temperature was raised to 145°C, and stirred at 250 rpm for 42 min under 0.32 MPa pressure. It is worth noting that this optimized process parameter enables the modified starch to show the best toughening effect.

[0135] In particular, the surface modification of nano-CaCO3 was carried out by stirring 60 nm nano-CaCO3 with 2.0% stearic acid at 85°C at a rate of 220 rpm for 2.2 h. This modification process significantly improved the surface activity of nano-CaCO3.

[0136] (2) Preparation of surface-modified silver nanoparticles

[0137] 0.02 mol / L silver nitrate solution was used as raw material, 1.0 wt% PVP was added as protective agent, and the reaction was carried out at 82°C for 32 min. Preferably, 3.0 wt% mercaptosilane coupling agent KH590 was added, and the modification was carried out at 62°C for 4.5 h. It is worth noting that the nanosilver prepared under this condition has the best particle size distribution and dispersion stability.

[0138] (3) Preparation of pH-sensitive dye system

[0139] Under strict nitrogen protection, 47 parts of styrene, 37 parts of acrylic acid, 21 parts of 2-aminoethyl methacrylate and 0.55 parts of AIBN were free radical polymerized at 77°C and 190 rpm for 6.5 hours. Further, the obtained copolymer was compounded with acid violet 49 at a mass ratio of 4.5:1 at 52°C for 2.2 hours. This optimized process parameter enables the pH-sensitive dye system to show the best response sensitivity.

[0140] (4) Matrix material blending

[0141] Under the conditions of 185℃ and vacuum degree -0.07MPa, the modified PLA and modified PHA were stirred at a rate of 240rpm for 42min. In particular, the selection of such process conditions enables the two polymers to be fully blended and form an ideal interpenetrating network structure.

[0142] (5) Functional component combination

[0143] Using a precisely controlled step-by-step heating program, add each functional component in turn:

[0144] a) From 180℃ to 200℃, the heating rate is 2.2℃ / min;

[0145] b) Continue heating to 250°C at a heating rate of 1.2°C / min;

[0146] c) Keep at 260°C for 32 min.

[0147] During the dispersion process, the optimized shear control program was used: the initial shear rate was 55s-1, the final shear rate was 210s-1, and the linear increase time was 16min. At the same time, the vacuum control program was: initial vacuum degree -0.022MPa, final vacuum degree -0.062MPa, and vacuum time 22min.

[0148] Finally, a precisely controlled cooling program was adopted: cooling from 250℃ to 180℃ at a rate of 3.2℃ / min, cooling from 180℃ to 100℃ at a rate of 5.2℃ / min, and natural cooling below 100℃.

[0149] The above four embodiments fully demonstrate the feasibility of the present invention and the optimization space of various technical parameters. It is worth noting that these embodiments cleverly achieve the synergistic effect between the various components of the material:

[0150] 1) The PLA / PHA blend system forms an ideal compatible structure through precisely controlled process parameters;

[0151] 2) The introduction of modified starch not only improves the degradation performance of the material, but also plays a toughening role;

[0152] 3) The combined use of nanosilver and pH-sensitive dyes produces an excellent synergistic effect, which not only ensures the antibacterial properties of the material, but also achieves precise response to the environmental pH;

[0153] 4) The multi-component system achieves good interface bonding through optimized process parameters.

[0154] The materials prepared in the above examples all exhibit excellent comprehensive performance and fully meet the requirements of relevant standards. In particular, the formula and process parameters in Example 4 achieve the best balance between antibacterial performance and intelligent color-changing function while maintaining high biodegradability.

[0155] Comparative Example 1

[0156] This comparative example is used to compare with Example 1, mainly to verify the effect of surface modification of nanosilver on the antibacterial properties of the material. While keeping other components and process parameters exactly the same as those in Example 1, nanosilver without surface modification is used in this comparative example.

[0157] Specifically, the material includes, by weight: 63 parts of a blend of PLLA and PDLA (other parameters are the same as in Example 1), 19 parts of P (3HB-co-4HB) copolymer, 17 parts of modified starch, 3.4 parts of unmodified nanosilver, 7.7 parts of pH sensitive dye system, 8.0 parts of silane coupling agent KH550 and 6.9 parts of kaolin.

[0158] In the preparation method, except for the nanosilver preparation step, the other steps are the same as those in Example 1. The nanosilver in this comparative example is directly prepared by chemical reduction method: 0.01 mol / L silver nitrate solution is reduced at 78° C. for 28 min, and only 0.5 wt % PVP is added as a protective agent without surface modification.

[0159] The test results show that due to the lack of surface modification steps, the dispersion of nanosilver in the matrix is ​​poor and the agglomeration phenomenon is obvious. This directly leads to a significant decrease in the antibacterial performance of the material, with an antibacterial rate of only 75%, far lower than 90.0% in Example 1. This result fully demonstrates the importance of surface modification to improve the dispersion and antibacterial effect of nanosilver.

[0160] Comparative Example 2

[0161] This comparative example is compared with Example 2, and focuses on verifying the effect of the PLA / PHA blending ratio on the mechanical properties and degradation properties of the material.

[0162] In this comparative example, the mass ratio of PLA / PHA is adjusted to 90:10 (much higher than the ratio in Example 2), and the specific components are: 85 parts of a blend of PLLA and PDLA, 10 parts of P(3HB-co-4HB) copolymer, 17.5 parts of modified starch, 3.6 parts of surface-modified nanosilver, 8.0 parts of pH sensitive dye system, 8.3 parts of silane coupling agent KH550 and 7.2 parts of kaolin.

[0163] The preparation method is basically the same as that of Example 2, but in the matrix material blending step, due to the significant increase in PLA content, the temperature is increased to 185° C. and the stirring time is extended to 45 min.

[0164] The test results show that too high a PLA content causes the material to become brittle, and the elongation at break is reduced by about 50%. At the same time, due to insufficient PHA content, the biodegradation rate of the material is significantly reduced, and the 90-day degradation rate is only 85%, which is far below the design index. This fully confirms the rationality of the PLA / PHA ratio in the present invention.

[0165] Comparative Example 3

[0166] This comparative example is compared with Example 3, and mainly verifies the influence of the copolymerization composition of the pH sensitive dye system on the color change performance. In this comparative example, the ratio of the copolymer monomers is adjusted to verify the rationality of the monomer ratio in the original scheme.

[0167] The specific components include, by weight: 66 parts of a blend of PLLA and PDLA, 20.5 parts of a P(3HB-co-4HB) copolymer, 18 parts of modified starch, 3.7 parts of surface-modified nanosilver, 8.2 parts of an improved pH-sensitive dye system (the monomer ratio is adjusted to: 55 parts of styrene, 25 parts of acrylic acid, 20.5 parts of 2-aminoethyl methacrylate), 8.5 parts of a silane coupling agent KH550 and 7.4 parts of kaolin.

[0168] In the preparation method, except for the preparation of pH sensitive dye, other steps are the same as Example 3. The preparation of pH sensitive dye adopts the same conditions, but due to the change of monomer ratio, the hydrophilicity of the obtained copolymer is significantly reduced. The test results show that due to the high styrene content, the density of pH sensitive groups is reduced, resulting in a significant decrease in the pH response sensitivity of the material, and the color difference △E*ab at 5°C is only 0.05, which cannot meet the requirements of rapid detection. This verifies the scientific nature of the monomer ratio in the original scheme of the present invention.

[0169] Comparative Example 4

[0170] This comparative example is compared with Example 4, and focuses on verifying the comprehensive influence of modified starch composition on material performance. In this comparative example, the starch is not modified with nano-CaCO3, and only ordinary starch and hydroxymethyl cellulose are used for compounding.

[0171] The material components are: 67 parts of a blend of PLLA and PDLA, 21 parts of P(3HB-co-4HB) copolymer, 18 parts of unmodified starch components (25 parts of ordinary corn starch, 2.2 parts of hydroxymethyl cellulose, 8.5 parts of deionized water), 3.8 parts of surface-modified nanosilver, 8.3 parts of pH-sensitive dye system, 8.6 parts of silane coupling agent KH550 and 7.5 parts of kaolin.

[0172] In the preparation method, the preparation steps of the modified starch are simplified as follows: corn starch is mixed with deionized water at 120°C, hydroxymethyl cellulose is added and stirred at 145°C. The test results show that due to the lack of the reinforcing effect of nano-CaCO3, the mechanical properties of the material are significantly reduced, and the tensile strength is reduced by about 30%. At the same time, the compatibility of starch with the polyester matrix is ​​poor, and obvious phase separation occurs, which not only affects the transparency of the material, but also leads to uneven degradation process.

[0173] Comparative Example 5

[0174] This comparative example verifies the influence of processing parameters on material properties by comparing Example 1 with Example 4. The composition ratio adopts the formula of Example 4, but the processing technology is simplified.

[0175] The step-by-step temperature increase program was cancelled during the preparation process, and the functional components were directly compounded at 250°C; at the same time, a constant shear rate of 180s-1 was adopted, and the programmed shear control was cancelled. The other parameters were the same as those in Example 4. The results showed that due to the lack of precise process control, the material showed obvious thermal degradation and the molecular weight decreased by about 20%. At the same time, the functional components were unevenly dispersed, resulting in significant fluctuations in both antibacterial properties and discoloration properties. This fully demonstrates the necessity of refined process control in the present invention.

[0176] Comparative Example 6

[0177] This comparative example is compared with Example 2, and focuses on verifying the influence of filler type on the comprehensive performance of the material. In this comparative example, kaolin is replaced with the same amount of talc.

[0178] In the material components, except that 7.2 parts of kaolin are replaced by 7.2 parts of talc, the other components and contents are exactly the same as those in Example 2. The preparation method is also the same as that in Example 2. The test results show that although talc can play a certain reinforcing role, due to its flaky structure, which is different from kaolin, the gas barrier performance of the material is reduced by about 40%. At the same time, talc has fewer surface functional groups, and the interface bonding with the matrix is ​​weak, and micropores are easily formed during the degradation process, which affects the service life of the material.

[0179] Through the systematic study of the above six comparative examples, the innovation and superiority of the present invention in the following aspects are fully verified:

[0180] 1) The antibacterial properties are significantly improved through surface modification of nanosilver;

[0181] 2) The optimal ratio of PLA / PHA achieves a balance between mechanical properties and degradation properties;

[0182] 3) The copolymer composition of pH-sensitive dye plays a key role in the color change sensitivity;

[0183] 4) The synergistic effect of multiple components of modified starch improves the comprehensive performance of the material;

[0184] 5) Accurate process control has a significant impact on material properties;

[0185] 6) Kaolin has unique advantages as a filler.

[0186] These results strongly support the creativity of the various technical features of the present invention and prove the scientificity and advancement of the invention scheme. It should be emphasized that it is the organic combination of these technical features that makes the material of the present invention exhibit excellent comprehensive performance. The applicant will design a series of test schemes to comprehensively evaluate the performance of the material of the present invention. The test content will revolve around the core innovation points of the material, focusing on verifying the synergistic effect of each component.

[0187] 1. Degradation performance test

[0188] Based on GB / T 20197-2006 standard, a systematic degradation performance evaluation scheme was designed. First, the samples of Examples 1-4 and Comparative Examples 1-6 were cut into specifications of 100mm×100mm×0.2mm, with 5 parallel samples in each group. The samples were placed in an incubator, and the temperature was controlled at 58±2°C and the relative humidity was 85±5%. Preferably, the mass loss rate was measured every 15 days, and the test was continued for 90 days. In particular, the morphological changes during the degradation process were observed by scanning electron microscopy (SEM), with an operating voltage of 15kV and a vacuum degree of 10 -4 Pa. Furthermore, gel permeation chromatography (GPC) was used to track the molecular weight changes, with tetrahydrofuran as the mobile phase, a flow rate of 1 mL / min, and a column temperature of 35 °C.

[0189] Through the above tests, it was found that the samples in Examples 1-4 all showed uniform volume degradation characteristics, which was due to the good compatibility of the modified starch with the polyester matrix. It is worth noting that the degradation rate after 90 days exceeded 99.8%, while in Comparative Example 2, due to insufficient PHA content, the degradation was uneven and the degradation rate was only 85%.

[0190] 2. Antibacterial performance test

[0191] According to GB20123-2008 standard, a comprehensive antibacterial performance evaluation system was designed. The test bacteria were Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 6538) and Aspergillus niger (ATCC 6275). First, the samples were cut into 25mm×25mm specifications, disinfected with 75% ethanol and dried. The concentration of the inoculated bacterial solution was controlled at 1.5×10 5 ~3×10 5 CFU / mL, inoculation volume 0.2mL. Bacteria were cultured at 37±1℃ for 24h, and fungi were cultured at 28±1℃ for 72h.

[0192] The test results show that the inhibition rate of the materials in Examples 1-4 against the three microorganisms is more than 90%, which is mainly due to the uniform dispersion of the surface-modified nanosilver. In contrast, the unmodified nanosilver used in Comparative Example 1 has an inhibition rate of only 75% due to severe agglomeration. In particular, transmission electron microscopy (TEM) observations show that the surface-modified nanosilver has a uniform particle size and good dispersion, which is the key to achieving high-efficiency antibacterial properties.

[0193] 3. Intelligent color change performance test

[0194] A color change performance test scheme simulating actual application scenarios was designed. The color difference was measured using a spectrophotometer (D65 standard light source, 10° observation angle), and the sample size was 50mm×50mm. The samples were placed in 5℃, 15℃, and 25℃ environments, and the relative humidity was controlled at 50±5%. The color difference value △E*ab was measured every 30 minutes and observed for 4 hours. At the same time, buffer solutions of pH 4.0, 5.0, 6.0, and 7.0 were used to evaluate the pH response sensitivity.

[0195] The experimental results show that the materials in Examples 3 and 4 can achieve significant color difference changes (△E*ab≥0.1) within 30 minutes at 5°C. However, in Comparative Example 3, due to the unreasonable copolymerization composition of the pH-sensitive dye, the response time was extended to more than 2 hours. Furthermore, the conformational changes of the pH-responsive groups were observed by in-situ infrared spectroscopy (ATR-FTIR), which provided direct evidence for the response mechanism.

[0196] 4. Mechanical properties and structural characterization

[0197] Based on a multi-scale characterization strategy, the mechanical properties and microstructure of the material were systematically evaluated. Conventional mechanical property tests were first performed, including tensile, bending and impact tests. In particular, dynamic mechanical behavior of the material was investigated in the range of -50 to 150 °C by dynamic thermomechanical analysis (DMA), with a heating rate of 2 °C / min and a frequency of 1 Hz.

[0198] Furthermore, small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WAXD) were used to characterize the microstructure of the material. The test conditions were: Cu target, working voltage 40kV, current 30mA, scanning range 2θ = 0.5 ~ 40°. The scattering pattern was collected by a two-dimensional detector, and the crystal structure was analyzed by combining Lorentz correction. At the same time, the phase distribution of each component was observed by the phase imaging mode of atomic force microscopy (AFM), with a scanning size of 2μm×2μm.

[0199] The experimental results show that the material in Example 4 exhibits the best balance of mechanical properties, which is due to the optimal ratio of PLA / PHA and the toughening effect of modified starch. The SAXS results show a clear long-period structure, indicating that the crystalline and amorphous regions are arranged in an orderly manner. The AFM phase diagram intuitively shows the uniform distribution of each component. In contrast, in Comparative Example 4, due to the lack of nano-CaCO3 modification, the interface between starch and the matrix is ​​poorly bonded, showing obvious phase separation.

[0200] Table 1 Basic performance test results of materials

[0201]

[0202]

[0203] Table 2 pH response performance and gas barrier test results

[0204]

[0205]

[0206] Table 3 Microstructure parameter characterization results

[0207]

[0208]

[0209] Based on the above test results, the present invention presents the following unexpected technical effects:

[0210] 1. Synergistic effect: Example 4 shows the best comprehensive performance, which is due to the synergistic effect of multiple innovations. In particular, the surface-modified nanosilver not only provides excellent antibacterial performance (95.2% antibacterial rate), but its uniformly dispersed nanoparticles also play a role in enhancing compatibility, which can be confirmed by the significant improvement of the interfacial shear strength (15.2MPa). This synergistic effect has not been reported in the prior art.

[0211] 2. Breakthrough in structure-performance relationship: By precisely controlling the phase structure of the PLA / PHA blend system, excellent mechanical properties (tensile strength 47.8MPa, elongation at break 275%) are achieved while maintaining high degradation performance (99.9%). This breaks the traditional understanding of the relationship between degradation and mechanical properties. Microstructure analysis shows that this is due to the unique interpenetrating network structure and nanoscale phase separation morphology.

[0212] 3. Innovation in response mechanism: The rapid response characteristics (20 min) and precise sensitivity (0.1 pH unit) exhibited by the pH-sensitive dye system far exceeded expectations. In-depth research found that this was due to the coordinated conformational changes of the copolymer segments, which not only accelerated the response speed but also improved the accuracy of the signal. In particular, it still maintained good responsiveness (△E*ab=0.20) under low temperature (5℃), which provides a new solution for cold chain monitoring.

[0213] 4. Processing technology breakthrough: Through optimized segmented heating and programmed shear control, the material properties are improved while the processing stability is significantly improved. This is reflected in the narrower nanosilver particle size distribution (10-15nm) and higher crystallinity (50.5%). In particular, this process optimization has brought unexpected improvements in gas barrier performance (oxygen permeability has dropped to 62cm 3 / m 2 ·24h·0.1MPa).

[0214] 5. Improved environmental adaptability: The multi-level structural design of modified starch not only provides a good toughening effect, but also gives the material excellent environmental adaptability. This is reflected in the wide glass transition temperature range and stable mechanical properties. In particular, under cyclic temperature and humidity conditions, the material still maintains structural stability, which provides an important guarantee for practical applications.

[0215] In summary, Example 4 embodies the best technical solution of the present invention, and its excellent performance is derived from the organic unity of multiple technical innovations. These unexpected technical effects fully demonstrate the creativity of the present invention and provide new research ideas for the development of bio-based smart packaging materials.

[0216] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. Degradable antibacterial intelligent color-changing printing packaging material, characterized in that: By weight, it includes the following components: 63-67 parts of a blend of PLLA and PDLA, wherein the mass ratio of PLLA to PDLA is 70:30 to 90:10; 19-21 parts of a P(3HB-co-4HB) copolymer, wherein the molar ratio of 3HB to 4HB is 85:15 to 95:5; 17-18 parts of modified starch; 3.4-3.8 parts of surface modified nanosilver; 7.7-8.3 parts pH sensitive dye system; 8.0-8.6 parts of silane coupling agent KH550; 6.9-7.5 parts of kaolin.

2. The packaging material according to claim 1, characterized in that: The blend of PLLA and PDLA has a D-isomer content of 0.5-2%, a stereoregularity of 98-99.5%, and a weight average molecular weight of 100,000-150,000.

3. The packaging material according to claim 1, characterized in that: The molecular weight distribution of the P(3HB-co-4HB) copolymer is 1.8-2.2, and the crystallinity is 55-65%.

4. The packaging material according to claim 1, characterized in that: The modified starch comprises the following components by weight: 21-23 parts of corn starch, wherein the amylose content is 23-27%; 6.5-7.5 parts of surface-modified nano-CaCO3 with a particle size of 40-60 nm; 1.8-2.2 parts of hydroxymethyl cellulose, with a degree of substitution of 1.6-2.0; 7.5-8.5 parts deionized water.

5. The packaging material according to claim 1, characterized in that: The pH sensitive dye system is compounded by a copolymer obtained by free radical polymerization of the following monomers in parts by weight and acid violet 49 in a mass ratio of 3.5:1 to 4.5:1: 43-47 parts of styrene; 33-37 parts of acrylic acid; 19-21 parts of 2-aminoethyl 2-methacrylate; 0.45-0.55 parts AIBN.

6. The method for preparing the degradable antibacterial intelligent color-changing printing packaging material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of modified starch: a) mixing corn starch with deionized water at 115-120° C. and 0.18-0.22 MPa, and stirring at a rate of 210-230 rpm for 33-37 min; b) adding surface-modified nano-CaCO3 and hydroxymethyl cellulose, heating to 135-145°C, stirring at 230-250 rpm for 38-42 min at 0.28-0.32 MPa; (2) Preparation of surface modified nanosilver: a) using 0.01-0.02 mol / L silver nitrate as raw material, using 0.5-1.0 wt% PVP as protective agent, reacting at 78-82° C. for 28-32 min; b) adding 2-3 wt% of mercaptosilane coupling agent KH590 and modifying at 58-62° C. for 3.5-4.5 h; (3) Preparation of pH sensitive dye system: Free radical polymerization was carried out at 73-77°C under nitrogen protection at a stirring rate of 170-190 rpm for 5.5-6.5 h, followed by compounding with Acid Violet No. 49 at 48-52°C for 1.8-2.2 h; (4) Matrix material blending: The modified PLA and the modified PHA were stirred at a rate of 220-240 rpm for 38-42 min at 175-185° C. and a vacuum degree of -0.05 to -0.07 MPa; (5) Functional component combination: Modified nanosilver, pH-sensitive dye system, coupling agent KH550 and kaolin were added in sequence, and a stepwise heating program was adopted: a) 180℃ to 200℃, heating rate 1.8-2.2℃ / min; b) 200°C to 250°C, heating rate 0.8-1.2°C / min; c) Keep at 240-260°C for 28-32 minutes.

7. The preparation method according to claim 6, characterized in that: The dispersion process in step (5) adopts a shear control procedure: The initial shear rate is 45-55s-1, The termination shear rate is 190-210s-1, The linear increase time is 14-16min.

8. The preparation method according to claim 6, characterized in that: The vacuum control procedure in step (5) is: The initial vacuum degree is -0.018 to -0.022MPa, The final vacuum degree is -0.058 to -0.062MPa. The vacuuming time is 18-22 minutes.

9. The preparation method according to claim 6, characterized in that: The cooling procedure after step (5) is: 250℃ to 180℃, cooling rate 2.8-3.2℃ / min; 180℃ to 100℃, cooling rate 4.8-5.2℃ / min; Natural cooling is adopted below 100℃.

10. The preparation method according to claim 6, characterized in that: The preparation method of the surface-modified nano-CaCO3 is as follows: Nano-CaCO3 with a particle size of 40-60 nm and stearic acid with a mass fraction of 1.5-2.0% are stirred at 75-85° C. at a speed of 180-220 rpm for 1.8-2.2 hours.

Citation Information

Patent Citations

  • High heat-resistant PLA / PHA composite material and preparation method thereof

    CN106467657A

  • Method for preparing polylactic acid stereocomplex by three-dimensional printing

    CN108285625A

  • Antibacterial biodegradable tableware and preparation method thereof

    CN112876745A

  • Method for improving crystallization capacity of polylactic acid copolymer material based on stereocompounding

    CN113861640A

  • Heat-resistant barrier polylactic acid composition as well as application and product thereof

    CN118909413A